Examining the Intention to Use Infant Health Monitoring Devices in South Korea - Mideum Choi; Seongcheol Kim (International Telecommunications Society (ITS), 2017)
The era of `Internet of Things' (IoT), in which all objects and the internet are connected and information is shared without human involvement, has arrived. According to <IoT Tech Road Map> published by SRI Consulting Business Intelligence in 2013, representative areas of IoT which will lead the market in 2017, include indoor positioning system applied to smart home and healthcare sector (SRI Consulting Business Intelligence, 2013). Gartner (2013) argued that global IoT market will produce economic value of 1.9 trillion dollar by 2020, and healthcare provider industry (15%) and manufacturing (15%) will account for the largest portion of the global IoT market. Healthcare industry is specifically expected to generate 285 billion dollar in added value, respectively (Gartner, 2013; KISDI, 2014). A number of specialists are considering healthcare industry as one of the areas where IoT technology will be most actively applied, and it is expected to form 'Mass Market; mass production and consumption' for consumers in the near future (Lee, 2014; BI Intelligence, 2013).
Keywords: 330